IN THE CORSET OF IDEOLOGY? PRESENTATIONS OF ‘THE OTHER’ IN MIDDLE SCHOOL TEXTBOOKS - Kaniewski, Jerzy (Porównania, 2018)
In the article I attempt to reconstruct the image of ‘the Other’ as presented in middle school textbooks. I am interested in how the authors introduce the motifs of otherness and cultural differences in the world as presented by the textbook. My analysis of five textbook series leads me to conclude that the image of ‘the Other’ is usually presented in contrast to patriotism developed by the official patriotic narrative and that the visions of ‘otherness’ shown to students are very different from the reality of the contemporary civilisation. It is difficult to resist the conclusion that school didactics have not moved beyond cultivating the 19th century concept of nation and beyond the outdated evidence of experiencing otherness developed in that culture. One cannot state with conviction that the education in Polish schools prepares the students for living in a multicultural society.